(3GdGbJUGO GdGSJKeGQ , GdCef , GdeLJeYs - (3eGQLQjJ Ce(B., (3HhdcSjs; (3OGQ GdJQLeI(B, s ((3HjQhJ(B:s (3GdOGQ GdYQHjI ddYdhe(B,s, 2009)
(3aj Xd HQjb fLeI NGaJI(B- (3CLRGA ef gfG hef gfGc(B- (3CgejI GdYbd(B- (3GdJacjQ GdeWdb(B- (3GdJeGS GdWQjb(B- (3ef Ybd Gdi Ybd(B- (3hYGO HQjb fLeJfG GdNGaJI(B.s
(3eQGLY U(B.165(3; ghGeT U(B.177s
Keywords: (3GdGSJKeGQs; (3GdGbJUGOs